PTH-016 Factors Associated with Upper Gastrointestinal Cancer Occurrence After OGD that Did Not Detect Cancer in The West Midlands. (17th August 2016) - Cheung, D; Rees, J; Evans, T; Trudgill, N
Abstract : Introduction: Up to 14% of upper gastrointestinal cancer (UGIC) subjects had an OGD that did not diagnose cancer up to 3 years prior to diagnosis. The rate of and associated risk factors for post-OGD upper gastrointestinal cancer (POUGIC) in the West Midlands were examined. Methods: Computerised OGD records from 8 NHS trusts in the West Midlands between 1998 and 2010 were retrieved and submitted to the West Midlands Cancer Intelligence Unit (WMCIU) for UGIC registrations linkage. Subjects undergoing OGD 3 to 36 months before diagnosis were identified as POUGIC and subjects with no OGD 3 to 36 months prior to diagnosis served as controls. The influence of age, gender, indication, endoscopist specialty, trainee involvement, sedation, number of biopsies taken from focal abnormalities, site and histology of UGIC on POUGIC were examined by logistic regression analysis. Results: 115, 113 OGD records were submitted to WMCIU and 3870 UGIC were linked. After exclusions, 2909 UGIC subjects were analysed. There were 275 (9.5%) POUGIC subjects (154 oesophageal cancer (OC) and 121 gastric cancer (GC)). The POUGIC rate ranged from 7.6 to 11.8% between the trusts. Of the POUGIC subjects, 143 (52.0%) had OGD 3 to 12 months and 132 (48.0%) 12 to 36 months prior to UGIC diagnosis. POUGIC subjects were younger (69.6±11.7 yrs) compared with controls (72.0±11.6 yrs) (p = 0.001). There were no association between POUGIC and OC or GC (GC OR 1.15, 95%CI 0.89–1.48, p = 0.289) or subject gender (female 1.14, 0.88–1.48, p = 0.312). Subjects with alarm symptoms (0.33, 0.26–0.43, p < 0.0001) were three times less likely to be associated with POUGIC. POUGIC subjects had less biopsies taken from focal lesions (4.2±2.2) compared with controls (5.4±2.6)(p < 0.0001). There was no association between POUGIC and endoscopist speciality (surgical 1.00, 0.71–1.40, p = 0.998) or nurse endoscopist (0.74, 0.43–1.29, p = 0.291). Trainee involvement was not associated with POUGIC (0.80, 0.60–1.07, p = 0.130). There were also no significant association between POUGIC and sedation (1.30, 0.97–1.76, p = 0.084) or sedation and topical anaesthesia (1.07, 0.76–1.49, p = 0.708), compared with topical anaesthesia alone. POUGIC subjects were more likely to undergo surgery (1.75, 1.33–2.29, p = 0.0001) but not chemotherapy (0.81, 0.62–1.06, p = 0.122) or radiotherapy (1.07, 0.79–1.46, p = 0.667). However, there was no significant survival difference at 1 yr (1.24, 0.97–1.60, p = 0.087) between POUGIC and controls. Conclusion: The POUGIC rate in the West Midlands was 9.5% between 1998 and 2010 and varied between 7.6 and 11.8% between trusts. POUGIC was associated with younger age, a lack of alarm symptoms and less biopsies from abnormalities. There was no significant survival difference between POUGIC subjects and controls at 1 yr. Disclosure of Interest: None Declared